Managing Fruit Splitting in Florida Citrus - Andrew Krajewski; Timothy Ebert; Arnold Schumann; Laura Waldo (EDIS)
Sometimes, the fruit on citrus trees will split open, making the fruit unmarketable; splitting can aid fungal and insect pests that subsequently damage fruit. A physiological disorder, pre-harvest fruit splitting begins with nutrient imbalances at flowering. Nutrient deficiencies weaken the rind, causing it to crack if interior parts of the fruit expand too quickly. Symptoms are only visible after it is too late to avoid the problem, but mitigation is still possible. Our goal is to define the problem and suggest management tactics for growers and Extension personnel to avoid or mitigate pre-harvest fruit splitting.